Large Firms as Threats to Small Business Survival in South Africa: An Exploratory Literature Review - Tendai Makwara (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Objective: This study examined how large businesses negatively impact small business survival and growth in South Africa. It aims to expose harmful practices by large firms that cause small businesses to fail. Thus it seeks to challenge a commonly held assertion that larger firms are predisposed to support smaller firms to achieve growth and survival objectives. Research Design & Methods: A theoretical literature review methodology was used to conduct this study. Findings: The findings indicate that many of the threats from South African large firms targeted at small, micro and medium enterprises (SMMEs) emanate from the advantage of their size, market dominance, and close links the corporate business sector enjoys with the government. Implications & Recommendations: The study argues that larger firms in South Africa are as much of a catalyst for the demise of SMMEs as they can also be beneficial. Therefore it recommends an effective administration of the Competitions Act laws to protect SMMEs and develop new policies that seek to build SMMEs in their capacity and not as a complementary sector to big companies. Contribution & Value Added: The study contributes to the overall discourse about the role of the large business community in supporting the SMME sector in the country. It thus adds value towards broadening an understanding of the threats to small business survival in South Africa and finding solutions of how they can be supported to become viable.